Kinematic determinants of acceleration in skeleton push phase - Gong, M.; Gao, C.; Tian, G.; Gao, B. (International Journal of Performance Analysis in Sport, 2021)
This study aimed to characterise the push phase kinematics in skeleton sport and explore the relationship between kinematic indicators and push performance. Nine male Chinese skeleton athletes performed three 15-metre pushes on an indoor simulated push track. Kinematic data were recorded with a 3-dimensional motion system (VICON; UK) consisting of 14 cameras sampling at a rate of 200 Hz. The linear relationships between the kinematic indicators and push performance were determined by Pearson correlation analysis. Statistical significance was set at p = 0.05. Step velocity (SV), step length (SL), toe-off distance (TOD), and toe-off angle (TOA) were significantly different between the inside and outside foot in the first four steps. Positively significant correlations were found between touchdown distance (TD), touchdown angle (TA), and SV in step 1 (r = 0.696; r = 0.682), and negative correlations were found between contact time (CT), TOA, and SV in step 1 and step 4, respectively (r = -0.839; r = -0.763). Effective acceleration was achieved by shortening contact, increasing TA and TD in the first step, and maintaining a relatively small TOA and a relatively long TOD in the steps 2 to 4.